Preparation and application of a seawater secondary battery using natural seawater as electrolyte

By using natural seawater as the electrolyte, new batteries with hexagonal phase molybdenum trioxide and copper hexacyanoferrate as electrode materials, the problems of limited resources of lithium-ion batteries and environmental pollution are solved, and efficient and environmentally friendly energy storage effects are achieved.

CN118448751BActive Publication Date: 2025-02-11UNIV OF JINAN
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410548951.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-06
Publication Date
2025-02-11
Estimated Expiration
2044-05-06

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have limited resources, high costs, poor safety and have a great impact on the environment, making it difficult to meet the needs of large-scale applications.

Method used

A new rechargeable battery is designed using natural seawater as the electrolyte, combined with hexagonal phase molybdenum trioxide and copper hexacyanoferrate as electrode materials. The battery can be free of electrolyte when it is not working, and seawater is injected to release electricity when it is working.

Benefits of technology

It realizes an environmentally friendly and low-priced energy storage solution, with good cycle stability and high energy density, and is suitable for backup power supply for offshore rescue and other offshore facilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118448751B_ABST
    Figure CN118448751B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of electrochemistry, and specifically relates to the preparation and application of a seawater secondary battery using natural seawater as an electrolyte, using hexagonal molybdenum trioxide as a negative electrode material, copper hexacyanoferrate as a positive electrode material, and natural seawater as an electrolyte to prepare a seawater battery that can be applied to a secondary battery. The secondary battery of the present invention has high energy density, good rate performance, and the raw materials are easily available and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemistry, and in particular relates to the preparation and application of a seawater secondary battery using natural seawater as electrolyte. Background Art

[0002] Due to the increasingly serious environmental pollution and continuous energy consumption, renewable energy and renewable energy storage technology are becoming increasingly important for social development and people's production and life. Seawater is one of the most abundant natural resources on the earth, covering two-thirds of the earth's surface, and contains abundant cation sources mainly composed of sodium ions. At the same time, electrochemical energy storage technology is a relatively clean energy storage method in energy storage systems. Although in the past few decades, lithium-ion batteries have been able to meet a wide range of applications due to their high energy density, good cycle stability and low self-discharge. However, limited lithium resources, high cost, poor safety and environmental impact have hindered the large-scale application of lithium-ion batteries. More and more researchers are committed to finding green, safe, low-cost and high-performance secondary batteries that can replace lithium-ion batteries. This requires continuous research and development of new battery technologies other than lithium-ion batteries, such as aqueous ion batteries. Therefore, a new type of rechargeable battery with low price, green and environmental protection and seawater as electrolyte is designed to effectively replace it. Summary of the invention

[0003] The present invention mainly provides a secondary battery energy storage system using natural seawater as electrolyte to solve the problems of limited lithium resources, high cost, poor safety and environmental pollution in the prior art. The technical solution is as follows:

[0004] A battery using natural seawater as electrolyte, comprising a negative electrode material and a positive electrode material, and seawater as electrolyte;

[0005] Furthermore, natural seawater is used as the electrolyte when the device is working, and there is or is no electrolyte when the device is not working.

[0006] Furthermore, the preparation of the hexagonal molybdenum trioxide comprises the following steps:

[0007] a. Slowly drip the hydrogen peroxide solution into the pure molybdenum powder and stir continuously at 0-5°C to obtain a yellow solution;

[0008] b. Dissolve ammonium nitrate in water to obtain an ammonium nitrate solution; add the ammonium nitrate solution to the yellow solution and perform a hydrothermal reaction at 150-220° C. for 20-28 hours, and after standing, washing, and drying, obtain hexagonal molybdenum trioxide.

[0009] Furthermore, the concentration of the hydrogen peroxide solution in step a is 30% w / w; the mass ratio of the molybdenum powder to the hydrogen peroxide in step a is 1:(6-7); the concentration of the ammonium nitrate solution in step b is 1.5-2.5M; the mass ratio of the ammonium nitrate to the molybdenum powder is 1:(3-4).

[0010] Furthermore, the continuous stirring time in step a is 1.5 to 2.5 hours; and the dripping rate of the hydrogen peroxide solution is 0.72 to 1.1 mL / min.

[0011] Furthermore, the preparation of the copper hexacyanoferrate comprises the following steps: slowly dripping a potassium ferrocyanide solution into a copper nitrate solution to obtain a mixed solution; mixing the mixed solution evenly and aging it at 40 to 50° C. for 4 to 8 hours, and obtaining the copper hexacyanoferrate material after standing, washing, and drying.

[0012] Furthermore, the potassium ferrocyanide solution is added at a rate of 0.72 to 1.1 mL / min.

[0013] Furthermore, the concentration of the potassium ferrocyanide solution in the system is 0.02-0.03M; the concentration of the copper nitrate solution in the system is 0.04-0.06M.

[0014] The preparation of the above-mentioned battery using natural seawater as electrolyte comprises the following steps:

[0015] 1) mixing the obtained hexagonal molybdenum trioxide with a conductive agent and then ball milling the mixture, mixing the ball milled powder with a binder, rolling the mixture into a film and pressing the film on a titanium mesh to form a negative electrode sheet;

[0016] 2) mixing the obtained copper hexacyanoferrate with a conductive agent and a binder, rolling the mixture into a film and pressing the film onto a titanium mesh to form a positive electrode sheet;

[0017] 3) Using dust-free paper as a separator, using natural seawater as an electrolyte or without an electrolyte, combining the negative electrode sheet of step 1) and the positive electrode sheet of step 2) to obtain a secondary battery.

[0018] Furthermore, the conductive agent is acetylene black; and the adhesive is PTFE.

[0019] An application of the above-mentioned battery using natural seawater as electrolyte in a secondary battery.

[0020] By adopting the above scheme, the method of the present invention has the following advantages:

[0021] 1. The present invention uses seawater as an electrolyte to realize a new energy storage platform for mutual conversion of electrical energy and chemical energy. Seawater is a renewable resource that is inexhaustible, so it has many advantages such as environmental protection and low price. It is also safer than organic electrolytes.

[0022] 2. The present invention can be used as a backup battery, stored in an electrolyte-free state, and when needed, electrical energy can be released by directly injecting seawater.

[0023] 3. The secondary battery of the present invention can be used as a backup power source for marine rescue, ships, vessels and other marine facilities.

[0024] 4. In the hexagonal molybdenum trioxide electrode material of the present invention, the open tunnel structure of molybdenum is conducive to the effective transfer of cations. When used as an electrode material in natural seawater electrolyte, it has good cycle stability. After 10,000 cycles, the capacity has almost no attenuation.

[0025] 5. When the hexagonal molybdenum trioxide electrode material of the present invention is subjected to a three-electrode test in a natural seawater electrolyte, when the current density is 1A·g -1 Specific capacity up to 204mAh g -1 , with very high energy density.

[0026] 6. The secondary battery of the present invention can be stored for a long time in a dry state, the raw materials are easy to obtain, the cost is low, the process is simple, and it is easy to produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope image of Example 1.

[0028] Figure 2 This is a transmission electron microscope image of Example 1.

[0029] Figure 3 This is the X-ray diffraction pattern of Example 1.

[0030] Figure 4 It is a cyclic voltammetry curve of the hexagonal molybdenum trioxide negative electrode sheet of Example 3 at different scan rates.

[0031] Figure 5 It is a constant current charge and discharge diagram of the hexagonal molybdenum trioxide negative electrode sheet of Example 3 at different current densities.

[0032] Figure 6 This is the rate charge and discharge diagram of the hexagonal molybdenum trioxide negative electrode sheet of Example 3.

[0033] Figure 7 The hexagonal molybdenum trioxide negative electrode sheet of Example 3 is 10A·g -1 Specific capacity curve of long cycle charge and discharge under current density.

[0034] Figure 8 The hexagonal molybdenum trioxide negative electrode sheet of Example 3 is 10A·g -1The specific capacity curve of long cycle charge and discharge when the battery is continuously taken out for drying and put back into seawater for continued charge and discharge at a certain current density.

[0035] Fig. 9 3 is a cyclic voltammetry curve of the secondary battery of Example 3 at different scan rates.

[0036] Fig.10 It is a constant current charge and discharge diagram of the secondary battery of Example 3 at different current densities.

[0037] Fig.11 This is a rate charge and discharge diagram of the secondary battery of Example 3. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Embodiment 1:

[0040] 12 mL of 30% w / w hydrogen peroxide aqueous solution was slowly added dropwise to 0.8 g of pure molybdenum powder at a rate of 1 mL / min, and stirred continuously in an ice-water bath for 2 h to obtain a yellow solution; the obtained yellow solution was added to 28 mL of 2M ammonium nitrate solution, and then transferred to a 100 mL autoclave and kept at 150° C. for 24 h; after naturally cooling to room temperature, the yellow product was alternately washed and centrifuged with deionized water and anhydrous ethanol for several times, and then dried under vacuum at 60° C. for 12 h to obtain a yellow powdery hexagonal molybdenum trioxide.

[0041] The obtained samples were characterized and the Figure 1 The scanning electron microscope images of different magnifications are shown. From the images, it can be seen that the sample morphology is a regular hexagonal rod structure, the particles are uniform, the surface is smooth and there is no agglomeration phenomenon.

[0042] Figure 2 TEM and HRTEM images of the sample. It can be seen from the images that the adjacent lattice spacing along the longitudinal direction of the obtained sample is 0.91nm.

[0043] The X-ray diffraction pattern of the obtained sample is as follows Figure 3 As shown, it can be seen from the spectrum that the diffraction peaks of the spectrum can correspond well to the standard card of hexagonal molybdenum trioxide, and the product has good crystallinity.

[0044] Embodiment 2:

[0045] 60 mL of 0.02 M potassium ferrocyanide solution was slowly added dropwise to 60 mL of 0.06 M copper sulfate trihydrate solution at a rate of 1 mL / min. The mixed solution was ultrasonicated for 20 min, then aged at 45 °C for 6 h, washed alternately with deionized water and ethanol, centrifuged several times, and the brown precipitate was collected and vacuum dried at 60 °C for 12 h. Brown copper hexacyanoferrate was obtained.

[0046] Embodiment 3:

[0047] (1) The hexagonal molybdenum trioxide powder obtained in Example 1 was mixed with acetylene black in a ratio of 6:3, and then ball-milled at a speed of 300 for 1 h. The ball-milled powder was mixed with PTFE in a ratio of 9:1, and rolled into a film and pressed on a titanium mesh to prepare a negative electrode sheet.

[0048] (2) The copper hexacyanoferrate powder obtained in Example 2 was mixed with acetylene black and PTFE in a ratio of 6:3:1 and rolled to form a film, which was pressed on a titanium mesh to prepare a positive electrode sheet.

[0049] (3) Using dust-free paper as a separator and seawater from the coast of Qingdao as an electrolyte, the negative electrode sheet of step (1) and the positive electrode sheet of step (2) are combined to obtain a secondary battery.

[0050] Electrochemical performance test:

[0051] The hexagonal molybdenum trioxide negative electrode sheet of step (1) of Example 3 was used as the negative electrode, the mercurous sulfate electrode was used as the reference electrode, and the platinum sheet was used as the counter electrode to conduct a three-electrode system test in natural seawater electrolyte. -1 CV was tested at scan rates of 1, 2, 5, 8, and 10 A·g -1 The GCD was tested to understand the reaction process and the charge and discharge capacity of energy storage. Figure 4-7 shown.

[0052] in, Figure 4 The hexagonal molybdenum trioxide electrode has a temperature range of 1-20 mV·s -1 From the cyclic voltammetry curves under scanning rate, it can be seen that there is a pair of significant Faraday redox peaks in the potential window of -1.3 to 0.2V (the reference electrode is Hg2SO4), indicating that a redox reaction occurs at the hexagonal molybdenum trioxide electrode; at the same time, with the increase of scanning rate, quasi-symmetric redox peaks and CV curves of similar shapes appear, showing that it has ideal pseudocapacitive properties and excellent rate performance; in addition, under this structure, ions can be inserted from the electrolyte into the center of the nanostructure, causing the anode peak in the nanostructure to move to a higher potential, while the cathode peak moves to a lower potential, indicating that relatively low resistance and rapid redox reactions can occur at the interface.

[0053] Figure 5 This is the constant current discharge diagram (GCD diagram) of the hexagonal molybdenum trioxide electrode, from which we can see the electrode / electrolyte charge transfer process and the electrochemical insertion-extraction process.

[0054] Figure 6 The relationship between the specific capacity and current density of the hexagonal molybdenum trioxide electrode is shown in Figure 2. It can be seen that when the current density is 1A·g -1 Specific capacity up to 204mAh g -1 , has excellent conductivity.

[0055] Figure 7 This is a long cycle stability test diagram of the hexagonal molybdenum trioxide electrode. It can be seen that after 10,000 cycles, the capacitance of the sample has hardly decreased, indicating that the seawater secondary battery of the present invention has excellent cycle stability.

[0056] Figure 8 In the long cycle test, the molybdenum trioxide electrode was taken out and dried after 1000 cycles and put back into seawater for further charge and discharge. During this period, the specific capacity did not change significantly, indicating that the seawater secondary battery of the present invention can be stored for a long time in a dry state without affecting its electrochemical performance.

[0057] The secondary battery obtained in step (3) of Example 3 was used for system testing. -1 CV was tested at scan rates of 1, 2, 5, 8, and 10 A·g -1 The GCD was tested to understand the reaction process and the charge and discharge capacity of energy storage. Figure 9-11 shown.

[0058] in, Fig. 9 The seawater secondary battery is 1~10mV·s -1 From the cyclic voltammetry curve under the scanning rate, it can be seen that there is a significant Faraday redox peak in the potential window of 0-1.8V, indicating that the seawater secondary battery has a redox reaction;

[0059] Fig.10 This is the constant current discharge diagram (GCD diagram) of the seawater secondary battery, from which we can see the electrode / electrolyte charge transfer process and the electrochemical insertion-extraction process.

[0060] Fig.11 This is the relationship between the specific capacity and current density of the seawater secondary battery. It can be seen that the battery has good conductivity.

[0061] For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present invention.

Claims

1. A battery using natural seawater as electrolyte, characterized in that: It comprises a negative electrode material and a positive electrode material, and seawater as an electrolyte; the negative electrode material is hexagonal molybdenum trioxide; the positive electrode material is copper hexacyanoferrate.

2. The battery using natural seawater as electrolyte according to claim 1, characterized in that: When the device is working, seawater is used as the electrolyte, and when the device is not working, there may or may not be an electrolyte.

3. The battery using natural seawater as electrolyte according to claim 1, characterized in that: The preparation of the negative electrode material comprises the following steps: a. Slowly drip the hydrogen peroxide solution into the pure molybdenum powder and stir continuously at 0~5℃ to obtain a yellow solution; b. Dissolve ammonium nitrate in water to obtain an ammonium nitrate solution; add the ammonium nitrate solution to the yellow solution and perform a hydrothermal reaction at 150-220°C for 20-28 hours, and then stand, wash, and dry to obtain the negative electrode material.

4. The battery using natural seawater as electrolyte according to claim 3, characterized in that: The concentration of the aqueous hydrogen peroxide solution in step a is 30% w / w; the mass ratio of the molybdenum powder to the hydrogen peroxide in step a is 1:(6-7); the concentration of the ammonium nitrate solution in step b is 1.5-2.5M; the mass ratio of the ammonium nitrate to the molybdenum powder is 1:(3-4).

5. The battery using natural seawater as electrolyte according to claim 3, characterized in that: The continuous stirring time in step a is 1.5 to 2.5 hours; the dropping rate of the aqueous hydrogen peroxide solution is 0.72 to 1.1 mL / min.

6. The battery using natural seawater as electrolyte according to claim 1, characterized in that: The preparation of the positive electrode material comprises the following steps: Slowly drip the potassium ferrocyanide solution into the copper nitrate solution at a rate of 0.72-1.1 mL / min while stirring to obtain a mixed solution; The mixed solution is mixed evenly and then aged at 40-50° C. for 4-8 hours. After standing, washing and drying, the positive electrode material is obtained.

7. The battery using natural seawater as electrolyte according to claim 6, characterized in that: The concentration of the potassium ferrocyanide solution in the system is 0.02-0.03M; the concentration of the copper nitrate solution in the system is 0.04-0.06M.

8. A method for preparing a battery using natural seawater as electrolyte according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) The obtained negative electrode material is mixed with a conductive agent and then ball-milled. The ball-milled powder is mixed with a binder, rolled into a film, and pressed on a titanium mesh to form a negative electrode sheet; 2) After mixing the obtained positive electrode material with a conductive agent and a binder, the mixture is rolled into a film and pressed onto a titanium mesh to form a positive electrode sheet; 3) Using dust-free paper as a separator, using natural seawater as an electrolyte or without an electrolyte, combining the negative electrode sheet of step 1) and the positive electrode sheet of step 2) to obtain a battery.

9. The method for preparing a battery using natural seawater as electrolyte according to claim 8, characterized in that: The conductive agent is acetylene black; the adhesive is PTFE.

10. Application of the battery with natural seawater as electrolyte according to claim 1 in a secondary battery, characterized in that: When the amount of electrolyte is insufficient to sustain charge and discharge, seawater electrolyte is added to the battery.

Citation Information

Patent Citations

  • Aqueous sodium-ion battery electrode plate, battery and preparation methods of aqueous sodium-ion battery electrode plate and battery

    CN115986122A

  • Sea water battery

    JP2014212111A

  • Method of manufacturing the electrodes of aqueous calcium ion-battery

    KR101993662B1